2020
DOI: 10.1002/ccd.28926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proximal balloon edge dilation technique for opening a side branch ostium in repetitive‐proximal optimizing technique sequence

Abstract: Objective: The purpose of this experimental bench test was to compare stent deformation, obstruction of stent struts at a jailed side branch (SB) ostium, and stent strut malapposition between SB inflation using proximal balloon edge dilation (PBED) technique and SB inflation using conventional balloon dilation in repetitive-proximal optimizing technique (re-POT) sequence. Background: The second proximal optimizing technique (POT) procedure in the re-POT sequence might increase obstruction of stent struts at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…5,6) However, the second POT procedure might reform the stent back to its original shape and pull well-deployed stent struts at the SB vessel wall toward the MB, thus, increasing obstruction by stent struts at a jailed SB ostium even when the PBED technique is used. 7,11) In the present study, a wide bifurcation angle would be associated with a higher rate of malapposed struts of the bifurcation segment after the PBED procedure. This negative phenomenon was observed more frequently with 2-link stents.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…5,6) However, the second POT procedure might reform the stent back to its original shape and pull well-deployed stent struts at the SB vessel wall toward the MB, thus, increasing obstruction by stent struts at a jailed SB ostium even when the PBED technique is used. 7,11) In the present study, a wide bifurcation angle would be associated with a higher rate of malapposed struts of the bifurcation segment after the PBED procedure. This negative phenomenon was observed more frequently with 2-link stents.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, link location at the SB ostium is an important factor for stent deformation in bifurcation PCI. [7][8][9] To avoid any influence of link location, we intentionally set the absence (linkfree) of stent links in the distal semicircle of the SB ostium under videoscopic observation in the present study. The differences in the rate of malapposed struts identified in our study might thus, be based on stent design, but not the location of wire re-cross or stent link.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have previously reported that the second POT procedure in the re-POT sequence increased obstruction of stent struts at a jailed SB ostium, because deformation of stent cells at the main branch occurred during SB inflation to open the SB ostium in our experimental bifurcation bench model study [ 5 ]. More recently, to prevent stent deformation during SB dilatation, our experimental bifurcation bench model study introduced the utility of SB inflation using the PBED technique and showed improved final results of cross-over single-stent implantation in bifurcation lesions using the POT-PBED procedures [ 2 ]. In the present case, OCT demonstrated well-apposed stent struts at both the proximal stent edge of the LMT and opposite the LCx after POT-PBED procedures, and a second POT (re-POT) procedure was not needed.…”
Section: Discussionmentioning
confidence: 99%
“…The default approach in bifurcation percutaneous coronary intervention (PCI) generally involves simple strategies with a single stent or provisional side branch (SB) stenting [ 1 ]. We previously reported an experimental bifurcation bench model study that showed good effects on obstruction by stent struts at a jailed SB ostium using a proximal balloon edge dilation (PBED) technique in the repetitive proximal optimizing technique (re-POT) sequence compared with conventional SB balloon dilation[ 2 ]. SB dilation with the PBED technique prevented stent deformation induced by SB dilation and eliminated the need for the second POT procedure in the re-POT sequence.…”
Section: Introductionmentioning
confidence: 99%